2018
DOI: 10.1007/s40858-018-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Delaying harvest for naturally drying maize grain increases the risk of kernel rot and fumonisin contamination

Abstract: Artificial drying, although costly, ensures a safe storage and preserves post-harvest grain quality. Alternatively, a more costeffective measure is to delay harvest to promote natural drying, but this management may increase the risk of mycotoxigenic ear rot fungi contamination. The objective was to evaluate the effect of increasing maize harvest delay on fungal disease and fumonisin levels. Three maize hybrids (BRS1035, Attack and DKB390 YG) were sown in the field to study the effect of five harvest delays (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Environments with higher temperatures may influence the production of high concentrations of fumonisin in maize (Rosa Junior et al 2019 ). Another study of Brazilian maize indicated that a GM hybrid with insect resistance (DKB390 YG) showed greater genetic resistance to the infection by F. verticillioides and fumonisin accumulation when compared with the other evaluated hybrids (da Costa et al 2018 ). However, within the hybrids used, no comparisons were made between the GM cv and the direct isogenic non-GM line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environments with higher temperatures may influence the production of high concentrations of fumonisin in maize (Rosa Junior et al 2019 ). Another study of Brazilian maize indicated that a GM hybrid with insect resistance (DKB390 YG) showed greater genetic resistance to the infection by F. verticillioides and fumonisin accumulation when compared with the other evaluated hybrids (da Costa et al 2018 ). However, within the hybrids used, no comparisons were made between the GM cv and the direct isogenic non-GM line.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce mycotoxin risk, hybrid selection criteria should include partial resistance to ear rot diseases, appropriate maturity range, husk coverage characteristics and adaptation to local conditions of abiotic stress (Munkvold 2014 ). da Costa et al ( 2018 ) demonstrated that delaying harvest for minimising drying costs may increase the risk of mycotoxin contamination in maize in the tropics of Brazil. Sampietro et al ( 2009 ) suggested that kernel factors are involved in resistance to fumonisin accumulation in the maize.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between the FUM content in maize and the delay (in days) of the harvest. It was also found that harvesting before the optimal harvest time, even though the crops were mature, resulted in reduced FUM formation [ 20 ]. This effect was also reported by Atukwase, et al [ 21 ] and Mansfield, et al [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher precipitation and lower temperatures before harvest and the delayed harvest of maize in different climate zones than ours have been observed to result in higher levels of Fusarium spp. and elevated mycotoxin contamination [ 24 , 25 , 26 ]. However, there is still a lack of information about the impact of delayed harvest time on maize grain infestation in our region.…”
Section: Introductionmentioning
confidence: 99%